The Girl from Chicago - Micheaux, Oscar; Orleans, Samuel; Mahon, Carl; Calloway, Starr; Brooks, Eunice (bfi, 2016)
"The Girl from Chicago" is a 1932 American Pre-Code drama film produced and directed by Oscar Micheaux, with an all-African American cast to include lead actor Carl Mahon. The story concerns a Federal agent who falls in love while on assignment in Mississippi. He helps his lover escape a local thug, and the film follows them to Harlem where they become involved in the assassination of a Cuban racketeer, played by Juano Hernández. Produced on a shoestring budget, this independent production featuring a largely non-professional cast, is known as one of the better-quality Micheaux productions. As is common in Micheaux's film, the story line is padded with several musical numbers, offering a glimpse of African American musical and dancing talent of the time. [wikipedia.org]
Keywords: DVD-Video